Liver Stiffness Measurement With FibroScan: Use the Right Probe in the Right Conditions!. Issue 4 (April 2019) - Berger, Arthur; Shili, Sarah; Zuberbuhler, Floraine; Hiriart, Jean-Baptiste; Lannes, Adrien; Chermak, Faiza; Hunault, Gilles; Foucher, Juliette; Oberti, Frederic; Fouchard-Hubert, Isabelle; Cales, Paul; de Ledinghen, Victor; et al.
Abstract : INTRODUCTION: FibroScan's M and XL probes give significantly different results, which could lead to misevaluation of liver fibrosis if the correct probe is not chosen. According to the manufacturer, the M probe should be used when the skin–liver capsule distance (SCD) is <25 mm, and the XL probe should be used when SCD is ≥25 mm. We aimed at validating this recommendation and defining the conditions of use for FibroScan probes in clinical practice. METHODS: Four hundred thirty-nine patients with biopsy-proven chronic liver disease were included. Of them, 382 had successful examinations with both M and XL probes. Advanced fibrosis was defined as Nonalcoholic Steatohepatitis Clinical Research Network (NASH CRN) F ≥3 or Metavir F ≥2. RESULTS: In a same patient, XL probe results were significantly lower than M probe results: 7.9 (5.6–11.7) vs 9.5 (6.7–14.6) kPa, respectively ( P < 0.001). After matching for age, sex, liver fibrosis, and serum transaminases, M probe results in patients with SCD <25 mm and XL probe results in those with SCD ≥25 mm did not significantly differ: 8.8 (6.0–12.0) vs 9.1 (6.7–12.8) kPa, respectively ( P = 0.175). Of note, 81.4% of patients with body mass index (BMI) <32 kg/m 2 had SCD <25 mm, and 77.7% of patients with BMI ≥32 kg/m 2 had SCD ≥25 mm. A practical algorithm using BMI first and then the FibroScan Automatic Probe Selection tool was proposed to help physicians accurately choose which probe to use in clinical practice. CONCLUSIONS: There is no significant difference in results between M and XL probes when they are used in the right conditions. In clinical practice, the probe should be selected according to the BMI and the Automatic Probe Selection tool.